The reactivity of plant‐derived organic matter and the potential importance of priming effects along the lower Amazon River. Issue 6 (14th June 2016) - Ward, Nicholas D.; Bianchi, Thomas S.; Sawakuchi, Henrique O.; Gagne‐Maynard, William; Cunha, Alan C.; Brito, Daimio C.; Neu, Vania; de Matos Valerio, Aline; da Silva, Rodrigo; Krusche, Alex V.; Richey, Jeffrey E.; Keil, Richard G.
Abstract: Here we present direct measurements of the biological breakdown of 13 C‐labeled substrates to CO2 at seven locations along the lower Amazon River, from Óbidos to the mouth. Dark incubation experiments were performed at high and low water periods using vanillin, a lignin phenol derived from vascular plants, and at the high water period using four different 13 C‐labeled plant litter leachates. Leachates derived from oak wood were degraded most slowly with vanillin monomers, macrophyte leaves, macrophyte stems, and whole grass leachates being converted to CO2 1.2, 1.3, 1.7, and 2.3 times faster, respectively, at the upstream boundary, Óbidos. Relative to Óbidos, the sum degradation rate of all four leachates was 3.3 and 2.6 times faster in the algae‐rich Tapajós and Xingu Rivers, respectively. Likewise, the leachates were broken down 3.2 times more quickly at Óbidos when algal biomass from the Tapajós River was simultaneously added. Leachate reactivity similarly increased from Óbidos to the mouth with leachates breaking down 1.7 times more quickly at Almeirim (midway to the mouth) and 2.8 times more quickly across the river mouth. There was no discernible correlation between in situ nutrient levels and remineralization rates, suggesting that priming effects were an important factor controlling reactivity along the continuum. Further, continuous measurements of CO2, O2, and conductivity along the confluence of the Tapajós and Amazon Rivers and the Xingu and Jarauçu Rivers revealed in situ evidence for enhanced O2 drawdown and CO2 production along the mixing zone of these confluences. Key Points: Biological conversion of 13 C‐labeled substrates to CO2 was tracked in the Amazon River Grasses were the most reactive followed by macrophyte stems, macrophyte leaves, and oak wood The presence of priming substrates enhanced leachate degradation rates by 1.5 to 6.0 times